Asymmetric syntheses of epohelmins A and B by In-mediated allylation. Issue 45 (2nd November 2016) - Liu, Yi-Wen; Han, Pan; Zhou, Wen; Mao, Zhuo-Ya; Si, Chang-Mei; Wei, Bang-Guo
Abstract : Natural products epohelmins A and B have been asymmetrically synthesized by In-mediated allylation of α-chiral aldimine with allyl bromide. Abstract : A diastereoselective new approach for the synthesis of trans -4-hydroxy-5-allyl-2-pyrrolidinone9 has been developed through In-mediated allylation of α-chiral aldimine8 with allyl bromide. The stereochemistry at the C-2 stereogenic center of9 was controlled by both the α-OTBS substitution and the sulfinamide moiety. The utility of this asymmetric allylation is demonstrated by the asymmetric syntheses of epohelmins A (4 ) and B (10 ).